Legal Protection for Consumers Victims of Illegal Online Loans in Indonesia: A Normative Study of Personal Data Misuse and Intimidating Billing Practices - Vivi Sylvia Purborini; Jusrihamulyono A.HM; Hilman Jayadi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The development of financial technology has expanded public access to financing services, yet it has also created opportunities for illegal online lending practices that harm consumers. This article analyses legal protection for consumers in illegal online lending, particularly regarding the misuse of personal data and intimidating debt collection practices that are often used as instruments of pressure against debtors. This study employs a normative juridical method with statutory and conceptual approaches. The legal materials examined include the Consumer Protection Law, the Personal Data Protection Law, the Electronic Information and Transactions Law, the Financial Sector Development and Strengthening Law, and regulations issued by the Financial Services Authority concerning consumer protection and information technology-based joint funding services. The findings show that illegal online lending creates complex legal problems because the violations are not limited to the absence of business licences, but also include violations of privacy rights, lack of information transparency, verbal threats, dissemination of personal data, and social pressure against consumers and third parties. Existing legal instruments provide an adequate normative basis for consumer protection, but their effectiveness remains limited because illegal actors operate outside the licensing system, frequently change their digital identities, and are difficult to reach through administrative supervision. Therefore, consumer protection must be implemented through an integrated preventive, repressive, and restorative approach. This article recommends strengthening inter-agency coordination, improving digital financial literacy, systematically blocking illegal applications, enforcing the law against personal data misuse, and restoring victims’ rights. These findings emphasise the importance of ensuring a balance between financial technology development, legal certainty, and the protection of consumer dignity within Indonesia’s increasingly complex digital economy.